2022
DOI: 10.3390/jcm11030601
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Outcome Prediction in Patients with Acute Myocardial Infarction

Abstract: (1) Background: Fibroblast growth factor 23 (FGF23) is associated with mortality in patients with heart failure (HF); however, less is known about mortality associations in patients with myocardial infarction (MI). (2) Methods: FGF23 was assessed in 180 patients with acute MI, 99 of whom presented with concomitant acute HF. Patients were followed up for one year, and outcome estimates by FGF23 were compared to GRACE score estimates. (3) Results: Log-transformed serum levels of intact FGF23 (logFGF23) did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…FGF23, however, lacked any discriminative capacity for predicting survival in patients without acute HF. 40 They demonstrated that in patients with acute HF caused by myocardial infarction, logFGF23 levels of 1.71 pg/mL accurately predicted death at 1 year with a sensitivity of 75% and a specificity of 74%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FGF23, however, lacked any discriminative capacity for predicting survival in patients without acute HF. 40 They demonstrated that in patients with acute HF caused by myocardial infarction, logFGF23 levels of 1.71 pg/mL accurately predicted death at 1 year with a sensitivity of 75% and a specificity of 74%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a later study by the same authors showed that, in patients with acute myocardial infarction and concomitant HF, FGF23 levels outperformed the Global Registry of Acute Coronary Events (GRACE) score in 1-year mortality prediction. FGF23, however, lacked any discriminative capacity for predicting survival in patients without acute HF 40. They demonstrated that in patients with acute HF caused by myocardial infarction, logFGF23 levels of 1.71 pg/mL accurately predicted death at 1 year with a sensitivity of 75% and a specificity of 74%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown a clear association between FGF23 level and CV morbidity and mortality in patients with HF rather than MI. German researchers conducted a study that indicated that FGF23 was linked to one-year mortality in patients with MI and concomitant acute HF [ 30 ]. Thorsen et al demonstrated that during the acute phase of MI, the level of FGF23 began to decline, with its normalization at seven days following revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown an association between high serum concentrations of FGF23 and cardiovascular mortality (37,45,(59)(60)(61)(62)(63)(64). Furthermore, the circulating concentrations of FGF23 are significantly higher in non-surviving patients with myocardial infarction and heart failure (65). A linear dose-response relationship between FGF23 concentration and cardiovascular mortality for concentrations of FGF23 of >50 pg/mL has been demonstrated (37,59).…”
Section: Fgf23 and Cardiovascular Mortalitymentioning
confidence: 98%